Dari Partisipasi Simbolik ke Keterlibatan Substantif: Peran Masyarakat sebagai Sumber, Pelaksana, dan Pengguna Hasil Pendidikan - Catharina Clariza Kartika; Nabila Fakhirah; Nur Kalimah Mahiroh; Ovinda Oktaviana (Saneskara: Journal of Social Studies, 2026)
Community participation in education still faces various obstacles, such as low levels of active involvement, a lack of communication between schools and the community, and the underutilization of the community in supporting education. This study aims to analyze the role of the community as a source, implementer, and user of educational outcomes. The study employs a qualitative approach using an integrative literature review method through the analysis of various journals, books, scientific articles, and policy documents relevant to the role of the community in education. The results indicate that the community serves as a source of education through the social and cultural environment, as an implementer of education through families, social organizations, and non-formal education, and as a user of educational outcomes who utilize and evaluate the quality of graduates. However, community participation remains largely administrative in nature and has not been optimally integrated into educational development, particularly in decision-making and providing feedback on educational outcomes. Therefore, this study underscores the importance of strengthening partnerships between schools and the community through collaborative forums, mapping community potential, and establishing feedback mechanisms from graduates to improve the quality and relevance of education. A limitation of this study is its reliance on secondary data sources, meaning that the findings depend on the scope and quality of the literature analyzed.